Creating Markets in Eswatini Strengthening the Private Sector to Grow Export Markets and Create Jobs - Country Private Sector Diagnostic (Private Sector Development, Privatization, and Industrial Policy, 2022)
Eswatini is facing multiple challenges. It was already experiencing weak economic growth before the COVID-19 pandemic, a reflection of longstanding, deeply rooted issues such as fiscal unsustainability, declining private investment, weakening productivity and competitiveness, and falling export diversification and complexity, compounded by the impact of climate shocks. It shifted from a private investment-led higher-growth model to a government spending-led lower-growth model after the end of apartheid in South Africa. With weak investment in productive sectors, Eswatini's job market failed to keep pace with an expanding, younger labor force, leading to a large informal sector. Eswatini's public sector-driven growth model is unsustainable under current fiscally constrained conditions, and there is a need to reduce and reprioritize public spending. An assessment of existing sectoral data and consultations with Eswatini's private sector and policy makers suggest that four sectors can help drive the export-led private sector growth model. To return to an export-led growth model, Eswatini needs to increase export competitiveness by advancing regulatory reforms and improvements in trade logistics that include regional collaboration to address trade facilitation constraints. Finally, given the country's vulnerability to climate risks, policies to foster economic resilience amid extreme weather events (mainly droughts that affect agriculture) and improve disaster preparedness need to be pursued. The private sector must adapt to this challenge and work with the government to improve climate resilience